The Bu Shen Yi Sui Formula Promotes Axonal Regeneration via Regulating the Neurotrophic Factor BDNF/TrkB and the Downstream PI3K/Akt Signaling Pathway - Zheng, Qi; Liu, Lei; Liu, Haolong; Zheng, Hong; Sun, Hao; Ji, Jing; Sun, Yaqin; Yang, Tao; Zhao, Hui; Qi, Fang; Li, Kangning; Li, Junling; et al. (Frontiers in Pharmacology, 2019)
Axonal damage is recognized as an important pathological feature in the chronic progressive neurological disorder multiple sclerosis (MS). Promoting axonal regeneration is a critical strategy for the treatment of MS. Our clinical and experimental studies have shown that Bu Shen Yi Sui formula (BSYS) promotes axonal regeneration in MS and experimental autoimmune encephalomyelitis (EAE), an animal model of MS, but the exact mechanism has not been thoroughly elucidated to date. In this study, we investigated the effects of BSYS and its two decomposed formulas—the Bu Shen formula (BS) and the Hua Tan Huo Xue formula (HTHX)—on brain-derived neurotrophic factor (BDNF) /TrkB and related signalling pathways to explore the mechanism by which axonal regeneration is promoted in vitro and in vivo. Damaged SH-SY5Y cells incubated with low serum were treated with BSYS-, BS- and HTHX-, containing serum, and EAE mice induced by the myelin oligodendrocyte glycoprotein (MOG) 35-55 peptide were treated with BSYS. The results showed that the BSYS-containing serum markedly increased cell viability and increased the levels of growth associated protein (GAP)-43, cAMP-response element binding protein (CREB), BDNF, TrkB and PI3K. The BS and HTHX treatments also induced the expression of GAP-43 and extracellular signal-regulated kinase (ERK) proteins in the cells. Furthermore, the effects of BSYS on cell viability, neurite outgrowth, and GAP-43 and CREB protein expression were clearly inhibited by LY294002, a specific antagonist of the PI3K signalling pathways. The addition of U0126 and U73122, antagonists of the ERK and PLCγ pathway, respectively, significantly inhibited cell viability and GAP-43 protein expression. Moreover, BSYS treatment significantly increased the expression of the 68, 160 and 200 kDa neuroﬁlament (NFs) of proteins and the BDNF, TrkB, PI3K and Akt mRNA and proteins in the brain or spinal cord of mice at different stages. These results indicated that BSYS promotes nerve regeneration, and its mechanism is mainly related to the upregulation of the BDNF/TrkB and PI3K/Akt signalling pathways. BS and HTHX also promoted nerve regeneration, and this effect involved the ERK pathway.